Membrane-bound Interleukin-1α mediates leukocyte adhesion during atherogenesis - Mäder, Christina; Speer, Timotheus; Wirth, Angela; Boeckel, Jes-Niels; Fatima, Sameen; Shahzad Hussain, Khurrum; Freichel, Marc; Laufs, Ulrich; Gaul, Susanne (Frontiers in immunology, 2023)
IntroductionThe interleukin-1 (IL-1) family and the NLR family pyrin domain-containing 3 (NLRP3) inflammasome contribute to atherogenesis but the underlying mechanisms are incompletely understood. Unlike IL-1β, IL-1α is not dependent on the NLRP3 inflammasome to exert its pro-inflammatory effects. Here, a non-genetic model was applied to characterize the role of IL-1α, IL-1β, and NLRP3 for the pathogenesis of atherosclerosis.MethodsAtherogenesis was induced by gain-of-function PCSK9-AAV8 mutant viruses and feeding of a high-fat western diet (WTD) for 12 weeks in C57Bl6/J wildtype mice (WT) and in Il1a-/-, Nlrp3-/-, and Il1b-/- mice.ResultsPCSK9-Il1a-/- mice showed reduced atherosclerotic plaque area in the aortic root with lower lipid accumulation, while no difference was observed between PCSK9-WT, PCSK9-Nlrp3-/- and PCSK9-Il1b-/- mice. Serum proteomic analysis showed a reduction of pro-inflammatory cytokines (e.g., IL-1β, IL-6) in PCSK9-Il1a-/- as well as in PCSK9-Nlrp3-/- and PCSK9-Il1b-/- mice. Bone marrow dendritic cells (BMDC) of PCSK9-WT, PCSK9-Nlrp3-/-, and PCSK9-Il1b-/- mice and primary human monocytes showed translocation of IL-1α to the plasma membrane (csIL-1α) upon stimulation with LPS. The translocation of IL-1α to the cell surface was regulated by myristoylation and increased in mice with hypercholesterolemia. CsIL-1α and IL1R1 protein-protein interaction on endothelial cells induced VCAM1 expression and monocyte adhesion, which was abrogated by the administration of neutralizing antibodies against IL-1α and IL1R1.ConclusionThe results highlight the importance of IL-1α on the cell surface of circulating leucocytes for the development of atherosclerosis. PCSK9-Il1a-/- mice, but not PCSK9-Nlrp3-/- or PCSK9-Il1b-/- mice, are protected from atherosclerosis after induction of hypercholesterolemia independent of circulating cytokines. Myristoylation and translocation of IL-1α to the cell surface in myeloid cells facilitates leukocyte adhesion and contributes to the development of atherosclerosis.